Pleiotropic Effects of Deubiquitinating Enzyme Ubp5 on Growth and Pathogenesis of Cryptococcus neoformans - Fang, Wei; Price, Michael S.; Toffaletti, Dena L.; Tenor, Jennifer; Betancourt-Quiroz, Marisol; Price, Jennifer L.; Pan, Wei-hua; Liao, Wan-qing; Perfect, John R. (PLOS ONE, 2012)
Ubiquitination is a reversible protein modification that influences various cellular processes in eukaryotic cells. Deubiquitinating enzymes remove ubiquitin, maintain ubiquitin homeostasis and regulate protein degradation via the ubiquitination pathway. Cryptococcus neoformans is an important basidiomycete pathogen that causes life-threatening meningoencephalitis primarily in the immunocompromised population. In order to understand the possible influence deubiquitinases have on growth and virulence of the model pathogenic yeast Cryptococcus neoformans, we generated deletion mutants of seven putative deubiquitinase genes. Compared to other deubiquitinating enzyme mutants, a ubp5Δ mutant exhibited severely attenuated virulence and many distinct phenotypes, including decreased capsule formation, hypomelanization, defective sporulation, and elevated sensitivity to several external stressors (such as high temperature, oxidative and nitrosative stresses, high salts, and antifungal agents). Ubp5 is likely the major deubiquitinating enzyme for stress responses in C. neoformans, which further delineates the evolutionary divergence of Cryptococcus from the model yeast S. cerevisiae, and provides an important paradigm for understanding the potential role of deubiquitination in virulence by other pathogenic fungi. Other putative deubiquitinase mutants (doa4Δ and ubp13Δ) share some phenotypes with the ubp5Δ mutant, illustrating functional overlap among deubiquitinating enzymes in C. neoformans. Therefore, deubiquitinating enzymes (especially Ubp5) are essential for the virulence composite of C. neoformans and provide an additional yeast survival and propagation advantage in the host.